CONTRASTIVE ANALYSIS OF ENGLISH AND BAHASA INDONESIA TRANSLATION ON ARABIC PRONOUN OF SURAH AL MUZZAMMIL - Rasi Yugafiati, - (2011)
The aim of this study was to contrast English and Bahasa Indonesia translation of Arabic pronoun in Surah Al Muzzammil after considering efforts were conducted to translate the Holy Quran, to increase understanding of content of it. A contrastive analysis was employed to describe the Arabic Pronoun (al- ismu ad-dhamiiry and its adjustments in English and Bahasa Indonesia translation of Surah Al-Muzzammil, This research was qualitative. To collect required data, the instrument used in this research is the Holy Quran, text books, an interview, In analyzing the data, the data that had been collected were tr b~... . a detailed description. The researcher also conducted library rese ~4.·ana·C.:qrmwt student. It was concluded that Arabic pronoun sometimes w re tratislated1 to''thi I English lecturers, Arabic assistant lecturer, and Bahasa Ind , ~sia. Depa.rti'D~ original meaning. In addition, Arabic plural pronouns sometimes-were translcttcif · to singular in English and Bahasa Indonesia. Therefore, it seems .both.of.them t, happened to get the naturalization. · -::...~